Morphological Analysis of “Bahasa Inggris Think Globally Act Locally” Book 2018 Revised Edition For 9th Grades by Ministry of Education and Culture - Muhamad Zacky Raimizard; Badriyah Ulfah; Jaya Nur Iman (CV. Ulil Albab Corp, 2022)
Morphological analysis helped to infer the meaning of several words, and, at the same time, learn new words. This research aims to find out, to count and to explain the kind of morpheme in Morphological Analysis of “Bahasa Inggris Think Globally Act Locally” Book 2018 Revised Edition for 9th Grades by Ministry of Education and Culture. The research method used qualitative method. To find out the data and count the result, this research used descriptive qualitative by calculating the percentages. The data displayed that free morpheme is the most common type of morpheme because free morpheme is a basic word. The number of words found was 19163 words spread over 209 pages, where bound morphemes were found as many as 3056 items which consisted of 39 items derivational prefixes, 993 items derivational suffixes, and 2024 items inflectional suffixes. It means, the result showed the use of Prefixes was only 1%. Meanwhile, the use of Suffixes was 99. Although the use of prefixes and suffixes was enequal, this book can still help students to enrich the vocabulary mastery with 30 types suffixes provides.